2017
DOI: 10.1103/physrevmaterials.1.064403
|View full text |Cite
|
Sign up to set email alerts
|

Role of entropy and structural parameters in the spin-state transition of LaCoO3

Abstract: The spin state transition in LaCoO3 has eluded description for decades despite concerted theoretical and experimental effort. In this study, we approach this problem using fully charge self-consistent Density Functional Theory + Embedded Dynamical Mean Field Theory (DFT+DMFT). We show from first principles that LaCoO3 cannot be described by a single, pure spin state at any temperature. Instead, we observe a gradual change in the population of higher spin multiplets with increasing temperature, with the high sp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 58 publications
2
14
0
1
Order By: Relevance
“…The transition occurs in a rather narrow range of p-d parameter variation (less than 0.1 eV), which indicates a high sensitivity of the cobalt ion spin state to the relative positions of the d and p states. These results are in good agreement with previous reports [42][43][44]59,60]. We also found that the weights of d 7 L states make a significant contribution to the total spin state, while the statistical weight of the intermediate d 6 state is about 10% and it remains almost constant through the spin-state transition.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…The transition occurs in a rather narrow range of p-d parameter variation (less than 0.1 eV), which indicates a high sensitivity of the cobalt ion spin state to the relative positions of the d and p states. These results are in good agreement with previous reports [42][43][44]59,60]. We also found that the weights of d 7 L states make a significant contribution to the total spin state, while the statistical weight of the intermediate d 6 state is about 10% and it remains almost constant through the spin-state transition.…”
Section: Resultssupporting
confidence: 93%
“…It was also found that a slight change in the degree of hybridization due to the proximity of the surface layer can induce a spin-state transition at any temperature in the observed region. This scenario agrees well with recently published works [43,59]. The experimental data obtained above 550 K can be well explained assuming a partial spin-state transition from a configuration with a dominant IS state into a configuration with a prevailing HS state.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Так, для иона кобальта в этом перовските возможны одновременно несколько типов спинового состояния и несколько типов зарядового состояния. Экспериментальные данные указывают на две важные модификации электронной структуры LaCoO 3 , происходящие по мере роста температуры системы: диамагнитный-парамагнитный спиновый переход около 100 K и фазовый переход полупроводник-металл между 350 и 650 К. Несмотря на большое количество работ в области физики кобальтита лантана, единое понимание электронных свойств и изменений магнитной конфигурации этой системы продолжает разрабатываться [25,26].…”
Section: исследования лазерно-индуцированных процессов в сурьме и кобunclassified